2004
DOI: 10.1111/j.1445-1433.2004.02998.x
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for elective general surgery: physical, psychological and social consequences

Abstract: There is a remarkable paucity of studies addressing the consequential impact of waiting for elective surgery on patients' health for each of the four studied disorders. Current literature permits merely general estimation of this consequential impact. As specific assessment of these consequences is important for daily practice and for policy, further research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
(133 reference statements)
0
39
0
3
Order By: Relevance
“…To our knowledge, this pilot program is the first of its kind to be reported in the literature. Long waiting lists for elective general surgery are common in other parts of the world, but the physical and social consequences have not been well documented [2], especially for those awaiting inguinal hernia repair. The cost burden for children with special needs has been demonstrated in those patients with congenital heart disease and cancer [3,4], but no analyses have been performed for healthy children awaiting elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this pilot program is the first of its kind to be reported in the literature. Long waiting lists for elective general surgery are common in other parts of the world, but the physical and social consequences have not been well documented [2], especially for those awaiting inguinal hernia repair. The cost burden for children with special needs has been demonstrated in those patients with congenital heart disease and cancer [3,4], but no analyses have been performed for healthy children awaiting elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological implications and care pathway quality assessment with a specific questionnaire and a quality score fragile and he has a state of great anxiety. This is the reason why, recently, special attention has been given to health service aspects which conditioned the medical care quality: Mitchell [12] focused the attention to the anxiety management in DS; Oudhoff et al [13,14] studied the patient psychological and social effects of the waiting list time and the need to the reduction of the waiting lists length to improve the health care service.…”
Section: Item Answers Scorementioning
confidence: 99%
“…4 During the waiting period, patient conditions may continue to worsen, leading to aggravated symptoms, and, therefore, leading to a negative impact on the mental health and quality of life of the patients. [5][6] The long wait times for scoliosis surgery can lead to serious consequences if the vertebral deformity progresses, such as increased curvature, rigid deformities, and thus, require more aggressive surgery to achieve an effective correction. 7 A recent study showed an increase in perioperative morbidity, increased surgical time, a greater need for blood transfusions, and a higher number of instrumented vertebrae.…”
Section: Introductionmentioning
confidence: 99%